Do fiscal rules constrain fiscal policy?: A meta-regression-analysis - Heinemann, Friedrich; Moessinger, Marc-Daniel; Yeter, Mustafa (European journal of political economy, 2018)
We implement a meta-regression-analysis for the budgetary impact of numerical fiscal rules based on 30 studies published in the last decade. The existing empirical evidence points to a constraining effect of rules on fiscal aggregates. However, this seemingly optimistic message is strongly weakened as our analysis points to a bias if the potential endogeneity of fiscal rules is not explicitly taken into account. Furthermore, our analysis provides evidence for the presence of a publication bias. Both sources of bias reduce the statistical precision of obtained effects below usual levels of statistical significance. In addition, we offer suggestive evidence for the effect size based on a small coherent sub-sample and provide recommendations for future research on the budgetary impact of fiscal rules.
Gesehen am 26.08.2019